#TITLE_ALTERNATIVE# - NATANAEL WIJAYA (NIM : 10208075); Pembimbing : Dr. rer. nat Bobby Eka Gunara, RIO
We present the four-dimensional manifold endowed with the metric of Joyces construction, which have torus symmetry. By using Levi-Civita connection, we calculate the curvature tensor and impose Einstein and maximally symmetric space (space of constant curvature) condition. From Einstein condition, we conclude that Joyce metric satifies Ricci at condition (lamdbda = 0). By imposing maximally symmetric space condition, we conclude that the solution is zero Gaussian curvature, that is, K = 0.